Assessing Jokowi’s First Term – ‘Jokowinomics’ : Has It Worked? - Guild, James (2019)
Joko Widodo, Indonesia’s seventh president, unveiled his first term in 2014 with an ambitious infrastructure development plan for both land and sea. Five years on, how should one assess the results of his administration’s economic policy?